2007
DOI: 10.1111/j.1553-2712.2007.tb01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Events during the Intrahospital Transport of Critically Ill Patients

Abstract: Unexpected events during the intrahospital transport of critically ill patients from the emergency department are common and can be potentially life threatening. Transporting physician experience is associated with UE rate. Strict adherence to and review of existing transport guidelines is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 14 publications
6
134
3
6
Order By: Relevance
“…Among trauma patients on mechanical ventilation, a study reported that 604 unexpected events occurred in 230 transports and 30 different types of physiological alterations were listed, such as severe hypotension, reduced intracranial pressure, cardiopulmonary arrest, pneumothorax, bronco aspiration, and chest pain, among others (14) .…”
Section: Physiological Alterations In the Critically Ill Patient Beinmentioning
confidence: 99%
See 1 more Smart Citation
“…Among trauma patients on mechanical ventilation, a study reported that 604 unexpected events occurred in 230 transports and 30 different types of physiological alterations were listed, such as severe hypotension, reduced intracranial pressure, cardiopulmonary arrest, pneumothorax, bronco aspiration, and chest pain, among others (14) .…”
Section: Physiological Alterations In the Critically Ill Patient Beinmentioning
confidence: 99%
“…The studies, in general, report a series of physiological alterations patients may experience during intrahospital transport, among them, increased heart rate (4,7,12) , altered blood pressure (4,7,12) , increased intracranial pressure (12) , arrhythmias (4,7,12) , heart attacks (12) , altered respiratory rate (4,12) , decreased oxygen satura-tion (4,7) , increase in airway pressure (7) , airway obstruction by secretion (7) , excessive coughing (7) , agitation (7) , bleeding (7), , hypo/hypercapnia (12) , hypoxemia (7,12) and cardiac arrest (7,14) . Change in blood pressure and cardiac rate are the most frequently found.…”
Section: Physiological Alterations In the Critically Ill Patient Beinmentioning
confidence: 99%
“…Conversely, Zuchelo and Chiavone 28 included these events and reported an incidence of 75.7% for adverse events. Papson et al 27 also included multiple types of events, including equipment problems and tangling of tubes/vascular access tubing, with unexpected events occurring in 67.9% of patients. In their formal recommendations for intrahospital transport, the Frenchlanguage society of intensive care describes the necessity to standardize these definitions.…”
Section: Adverse Events During Transportmentioning
confidence: 99%
“…5,[24][25][26][27][28] This wide variation is largely based on differences in definitions of adverse events. As an example, in the study by Kue et al, 24 who reported an overall adverse event rate of 1.7%, technical events such as losing an intravenous catheter or equipment malfunction were excluded as adverse events.…”
Section: Adverse Events During Transportmentioning
confidence: 99%
“…This means that patients may be transferred to different sections of the hospital without changing the modality and parameters of their ventilatory support. It is notable that while unexpected events during the intra-hospital transfer of critical patients receiving conventional ventilation have been extensively reviewed (4,(12)(13)(14)(15), few recommendations regarding patients receiving NIV support are available.…”
Section: Introductionmentioning
confidence: 99%